Synthesis and Antibacterial Activity of Stilbene Derivatives - Yilkal Matebie (ASTU, 2018)
The stilbene scaffold is a basic element for a number of biologically active natural and synthetic compounds, and it is considered as a privileged structure. Stilbene derivatives have reported to have enormous biological activities including antimicrobial, antifungal, antioxidant, hepatoprotective, anti-viral, cytotoxic, anti-inflammatory and antiplatelet. The current research project is therefore designed to synthesize methoxy, chlorine and nitro containing stilbene derivatives and evaluated their antibacterial activities. In view of this substituted stilbene derivatives were prepared from benzyl triphenyl phosphonium chloride and substituted benzaldehyde using Wittig reaction. The compounds were obtained in yields ranging from 64-92 % .The structures of the synthesized compounds viz stilbene, 4’-nitrostilbene, 4’-methoxystilbene, 4’-chlorostilbene, 3’,4’-dichlorostilbene, 4’’-methoxy-4’-nitrostilbene and 4’-chloro-4’’methoxystilbene were done employing spectroscopic methods including NMR (1H-NMR and 13CNMR) and FT-IR. Furthermore, the synthesized compounds were evaluated for their in vitro antibacterial activity against one Gram-positive strains (Staphylococcus aureus) and three Gram-negative strains (Escherichia coli, P. aeroginosa and K. puemonia) using disc diffusion method. Compoud 3’,4’-dichlorostilbene displayed pronounceable activity against S. aureus and E.coli with inhibition zones of 24 mm and 22 mm, respectively. The result is significant compared with ceftriaxone used as positive control.